Study guides

☆☆

Q: 2a plus 3b - 4a plus 5b?

Write your answer...

Submit

Still have questions?

Related questions

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

The expression is: (4a+b)/(2a-5b)

3a - 2b

2a+6b

3a - 2b

2a+5b isn't possible the answer is still 2a+5b.

What is the solution of -2a plus 3a plus 5b

5ab-2ab+4a-b+5b = 3ab+4a+4b

5b plus 5-3b-7 is 2b-2.

We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.

(1) 4a-5b=7 (2) 4a+5b=17 (1)-(2) gives 4a-5b-(4a+5b)=7-17 then -10b=-10 so b=1 from (2) one gets 4a=17-5b=17-5x1=12 so a=3 (3,1) is the solution

5b + 11 - 2b = 3b + 11

4a - 5b = 74a +5b = 17From the first equation:4a = 7 + 5bsubstitute this value in the second equation:7 + 5b + 5b = 177 + 10b = 1710b = 10b = 1Now,solve for a :4a - 5(1) = 74a = 7 + 54a = 12a = 3

Add the equations: 4a + 4a - 5b + 5b = 7 + 17 ie 8a = 24 a = 3, so b = 1

here is how you go about solving it first write down the question 3b+4+5b-1 then change arrangement so that it looks like this 3b+5b+4-1 then solve 8b+3

5+3b? :3

(4, 3)

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

4(a+5b)

A level 5a is higher. This is how it works: n 1c 1b 1a 2c 2b 2a 3c 3b 3a 4c 4b 4a 5c 5b 5a ect. Student from BGP. N.S.S

ACCORDING TO MY SHOP MANUAL: 1A-6B-5A-2B-3A-4B-6A-1B-2A-5B-4A-3B A is RH bank, B is LH bank as viewed from the front.

3(7a - 5b) + 2(4a - 3b) Multiply the contents of each bracket by the number outside it: 21a - 15b + 8a - 6b Bring like terms together: 21a + 8a - 15b - 6b Combine like terms: 29a - 21b This cannot be simplified further.

(ab/b) / (4a/5b) =(ab / b) * (5b / 4a) = (5ab2 / 4ab)= 5 / (4b)

It is 9